Self-instruction checklists and addition skills of students with mild mental retardation - Mina, Jennilyn Grace C. (Quezon City College of Education, University of the Philippines Diliman, 2008)
The study focused on the use of self-instruction checklists as a metacognitive approach in teaching students with mild mental retardation. Participants included 5 mainstreamed, third-grade students from Batino Elementary School. The study lasted for a month, including the pretesting and posttesting. Results of the study showed that self-instruction checklists increased the metacognitive skills of the students and improved their performance in solving addition with regrouping. This study recommends the metacognitive scaffolding as an instructional method in teaching students with mild mental retardation in the area of problem solving.
Thesis (Master of Arts in Education : Special Education)--University of the Philippines, Diliman
Keywords: Metacognition in children -- Philippines -- Quezon City; Children with mental disabilities -- Philippines -- Quezon City; Mathematics -- Study and teaching (Elementary) -- Philippines -- Quezon City